Laparoscopic esophageal myotomy versus pneumatic dilation in the treatment of idiopathic achalasia: a meta-analysis of randomized controlled trials - Baniya R; Upadhaya S; Khan J; Subedi SK; Shaik Mohammed T; Ganatra BK; Bachuwa G (Clinical and Experimental Gastroenterology, 2017)
Ramkaji Baniya, Sunil Upadhaya, Jahangir Khan, Suresh Kumar Subedi, Tabrez Shaik Mohammed, Balvant K Ganatra, Ghassan Bachuwa Department of Internal Medicine, Hurley Medical Center, Michigan State University, Flint, MI, USA Background: Achalasia is a primary esophageal motility disorder of unknown etiology associated with abnormalities in peristalsis and lower esophageal sphincter relaxation. The disease is incurable; however, definitive treatment procedures like pneumatic dilation (PD)/balloon dilation and laparoscopic esophageal myotomy (LEM) are performed to relieve dysphagia and related symptoms. Currently, there is paucity of data comparing the outcomes of these procedures. The aim of this meta-analysis is to compare the short- and long-term success rates of PD and LEM. Methods: A thorough systematic search of PubMed, Scopus, clinicaltrials.gov, and Cochrane library was conducted for randomized controlled trials (RCTs) comparing the outcomes of PD versus LEM in the treatment of achalasia. The Mantel-Haenszel method and random effect model were used to analyze the data. RCTs with outcome data at 3-month, 1-year, and 5-year intervals were analyzed. Results: A total of 437,378 and 254 patients at 3-month, 1-year, and 5-year intervals were analyzed for outcome data. At 3 months and 1 year, PD was not as effective as LEM (odds ratio [OR]: 0.50; confidence interval [CI] 0.31–0.82; P = 0.009 and OR: 0.47; CI 0.22–0.99; P = 0.21) but at 5 years, one procedure was non-inferior to the other (OR: 0.62; 0.33–1.19; P = 0.34). Conclusion: PD was as effective as LEM in relieving symptoms of achalasia in the long-term. Keywords: achalasia, balloon dilation, pneumatic dilation, laparoscopic myotomy, Heller’s myotomy